2020
DOI: 10.3390/ijms21030988
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of the Aqueous Extract of Deschampsia antarctica (EDAFENCE®) on Skin Cells against Blue Light Emitted from Digital Devices

Abstract: Skin is being increasingly exposed to artificial blue light due to the extensive use of electronic devices. This, together with recent observations reporting that blue light—also known as high-energy visible light—can exert cytotoxic effects associated with oxidative stress and promote hyperpigmentation, has sparked interest in blue light and its potential harmful effects on skin. The photoprotective properties of new extracts of different botanicals with antioxidant activity are therefore being studied. Desch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…All primer sequences used in this study were as follows: IL-6 forward: 5 -ATG AAC TCC TTC ACA AGC-3 , reverse: 5 -GTT TTC TGC CAG TGC CTC TTT G-3 (Bio Basic Canada Inc., Ontario, Canada). IL-8 forward, 5 -CTC TGT GTG AAG GTG CAG TTT TG-3 , reverse, 5 -TCT CTT CCA TCA GAA AGC TTT ACA ATA-3 ; COL1A1 forward, 5 -TGA GCC AGC AGA TCG AGA-3 reverse, 5 -ACC AGT CTC CAT GTT GCA GA-3 ; MMP1 forward, 5 -TCT GAC GTT GAT CCC AGA GAG CAG-3 reverse, 5 -CAG GGT GAC ACC AGT GAC TGC AC-3 and GAPDH forward, 5 -TCA ACA GCG ACA CCC AC-3 reverse, 5 -TCA ACA GCG ACA CCC AC-3 (Humanizing Genomics Macrogen, Geumcheon-gu, Seoul, South Korea) [56][57][58].…”
Section: Expression Of Il-6 Il-8 Col1a1 and Mmp1 Genes By Rt-qpcr Ana...mentioning
confidence: 99%
“…All primer sequences used in this study were as follows: IL-6 forward: 5 -ATG AAC TCC TTC ACA AGC-3 , reverse: 5 -GTT TTC TGC CAG TGC CTC TTT G-3 (Bio Basic Canada Inc., Ontario, Canada). IL-8 forward, 5 -CTC TGT GTG AAG GTG CAG TTT TG-3 , reverse, 5 -TCT CTT CCA TCA GAA AGC TTT ACA ATA-3 ; COL1A1 forward, 5 -TGA GCC AGC AGA TCG AGA-3 reverse, 5 -ACC AGT CTC CAT GTT GCA GA-3 ; MMP1 forward, 5 -TCT GAC GTT GAT CCC AGA GAG CAG-3 reverse, 5 -CAG GGT GAC ACC AGT GAC TGC AC-3 and GAPDH forward, 5 -TCA ACA GCG ACA CCC AC-3 reverse, 5 -TCA ACA GCG ACA CCC AC-3 (Humanizing Genomics Macrogen, Geumcheon-gu, Seoul, South Korea) [56][57][58].…”
Section: Expression Of Il-6 Il-8 Col1a1 and Mmp1 Genes By Rt-qpcr Ana...mentioning
confidence: 99%
“…The spontaneously immortalized human cell line HaCaT exhibits normal morphogenesis and expresses all the major surface markers and functional activities of isolated keratinocytes; for this reason, HaCaT will be chosen as a model for the study of keratinocytes functions and for investigating the effects of the compounds of interest on an epidermal model. Lorrio et al demonstrated that a natural aqueous extract of Deschampsia antarctica protects skin against artificial ad natural light by reducing the production of ROS and hyperpigmentation in fibroblasts and melanocytes [11]. In this study, the chemical composition of the natural aqueous extract of Deschampsia antarctica was not described, while in our work, we obtained a phytocomplex highly strandardized in polyphenol content using the cell culture technology.…”
Section: Discussionmentioning
confidence: 58%
“…Skin is being increasingly exposed to artificial blue light due to the extensive use of electronic devices. This, together with recent observations reporting that blue light can exert cytotoxic effects associated with oxidative stress and promote hyperpigmentation, has sparked interest in blue light and its potential harmful effects on skin [11]. Several studies report that blue light contributes to skin aging and carcinogenesis, mostly during direct sunlight exposure, similar to UVA [12].…”
Section: Introductionmentioning
confidence: 99%
“…As aforementioned, an increasingly studied agent challenging skin homeostasis in modern life is highenergy blue light, a radiation wavelength emitted by digital devices and therefore reaching our body for extensive periods of time. Recent studies [85] mimicking artificial blue light exposure on in vitro cell cultures revealed that these wavelengths reduce cell viability (an effect more pronounced in melanocytes than in dermal fibroblasts), promote hyperpigmentation and morphological alterations, and induce mitochondrial dysfunction and oxidative stress. Of note, addition of Edafence® counteracted these effects and reduced oxidative stress and ROS accumulation, mitochondrial homeostasis, and stress markers in fibroblasts, as well as melanization of keratinocytes [85] .…”
Section: Light Radiationsmentioning
confidence: 99%
“…Scale bar: 50 µm. Adapted from [81,84,85] . UVB: ultraviolet B radiation; VIS: visible light spectrum; wIRA: infrared spectrum…”
Section: Light Radiationsmentioning
confidence: 99%